Innovative actions in oceans and human health for Europe - Pellens, Noortje; Boelee, Eline; Veiga, Joana M; Fleming, Lora E; Blauw, Anouk (Health promotion international, 2023)
Summary Innovative actions are local initiatives which leverage the interactions between the ocean and human health to reduce the risks and enhance the benefits for the stakeholders and the natural environment. These initiatives can have strong positive effects on human health and wellbeing as well as on the marine environment. We analysed 150 such innovative actions in Europe. Using a combined case study and survey approach, innovative actions were identified using interviews and content analysis of websites and compiled into a database. Quantitative data were analysed according to the Drivers, Pressures, State, Impact and Response (DPSIR) framework, guided by selected in-depth interviews. Overall, the innovative actions provided a positive impact on the health of both the ocean and humans through increasing food provision, water quality and tourism opportunities; and addressing environmental issues such as commercial fish stock depletion, pollution and climate change. Innovative actions contributed to meeting various targets of the Sustainable Development Goals (SDGs) 3, 13 and 14. These actions played a potential role ahead of and alongside policy. Some of the innovative actions may have potential to be put in place elsewhere. Such up-scaling would need to be adapted to local circumstances and could be facilitated by an innovative action exchange platform. Lay Summary This study presents 150 innovative actions taken by citizens and organizations in Europe to promote the health of both the ocean and humans. These were analysed and categorized according to the environmental issues they responded to, the Sustainable Development Goals (SDGs) addressed, and the ecosystem services provided. Plastic pollution and loss of biodiversity were the most targeted environmental issues, while tourism, recreation and wellbeing were the services most addressed by the innovative actions. These innovative actions tended to target those SDGs that currently show a lack of progress. Such actions, with both an environmental and health promotion agenda, may have the potential to complement regular policymaking in achieving these SDGs. The impact could be further enhanced by sharing best practices among an international network of local stakeholder action innovators. An interactive map shows the locations and websites of the European innovative actions identified. The map can serve as a first step in providing a platform for the network to connect and inspire people interested in creating their own interventions.